Knowledge, attitude, perception and practices in respect of rabies disease among the residents in Ga East municipality, Ghana - Oscar, Vetsi (2020)
A thesis submitted to the School of Public Health, College of Health Sciences, in partial fulfilment of the requirement for the award of a Bachelor Degree and Public Health.